Beliefs About Causes and Cures of Prolonged Grief Disorder Among Arab and Sub-Saharan African Refugees - Lechner-Meichsner, Franziska; Comtesse, Hannah (Frontiers in Psychiatry, 2022)
Background. Many refugees have experienced the death of a loved one under traumatic circumstances. Accordingly, the prevalence of Prolonged Grief Disorder (PGD) among refugees is high. Culture-specific symptoms of PGD have been described previously, but beliefs about causes and cures of PGD among refugees remain unknown. We therefore aimed at identifying illness beliefs and treatment expectations regarding PGD among refugees. Method. We focused on refugees from Arab countries (n = 14) and from Sub-Sahara Africa (n = 9) and applied qualitative and quantitative methods. In a semi-structured interview, participants first answered questions about assumed causes and potential cures for prototypical PGD symptoms according to ICD-11 that were presented in a vignette as representatives of their own culture. In the quantitative part, they completed the Cause Subscale of the Illness Perception Questionnaire (IPQ-R) that included additional culture-specific items. Interviews were analyzed with Qualitative Content Analysis. Results. In both groups of refugees, PGD symptoms were predominantly attributed to a close relationship to the deceased, lack of social support, personal vulnerabilities, and circumstances of the death. Participants also named a number of flight-related causes (e.g., inability to perform or participate in rituals, feeling isolated in the host country). None of the participants attributed PGD symptoms to supernatural causes. Descriptive analyses of responses on the IPQ-R indicated that participants predominantly attributed PGD symptoms to psychological causes. Participants believed that PGD can be cured and predominantly mentioned social and religious support. Psychological help was only mentioned by a minority of participants. In both groups, participants emphasized that a therapist must be familiar with the patient’s culture and rituals. Participants also mentioned stigma associated with seeking psychological help. Conclusion. Results suggest specific beliefs of refugees regarding causes and cures of PGD as well as similarities with Western conceptualizations. A culture-sensitive approach to the treatment of PGD in refugees that can include knowledge of culture-specific rituals and incorporating religious beliefs as well as decreasing stigma and increasing mental health literacy seem important. The study is limited by its focus on only two groups of refugees and its small sample size.